How can the potential harms of loot boxes be minimised?: Proposals for understanding and addressing issues at a national level - Macey Joseph; Cantell Mikko; Tossavainen Tommi; Karjala Antti; Castrén Sari (Hungary, 2025)
Background and aims
Loot boxes are in-game items which distribute rewards to players via random-number generation; many games require players to make in-game payments to access their contents. The combination of financial outlay and random rewards has raised concern about similarities to gambling. This debate paper presents a series of themes identified by an inter-institutional working group in Finland, alongside suggested actions, and are presented with the intention of stimulating debate among stakeholders.
Methods
This work uses an exploratory research approach to gather data from a range of sources, including state-of-the-art reports from several fields and qualitative content analysis of invited presentations from a range of stakeholders, including affected individuals, practitioners, and field-specific experts.
Results and Discussion
Several significant themes emerged from the work and are presented alongside a series of proposed action points. Based on this preliminary exploration we propose a series of, non-exhaustive, actions for both primary and secondary prevention. Furthermore, the group identified the potential for responsible gaming practices to be adopted which would help to minimize the harm from overspending in gaming activities. Finally, we identified the need for further research in the field, for example the use of player data and both longitudinal and qualitative studies.
Conclusions
The emergent themes are discussed in relation to both the views of the presenters and existing research in the field and are intended to promote discussion concerning the viability of context-specific approaches to an issue of global reach and significance